Isu Strategis Tata Kelola Pembangunan Berkelanjutan (Studi pada Kabupaten Sampang, Provinsi Jawa Timur) - Wijaya, Andy Fefta; Ulum, Mochamad Chazienul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Sustainable development seeks to equitably distribute development outcomes across various groups and layers of society and among generations. The prerequisite for achieving sustainable development is environmentally sound development. It means that development is compatible with the environment so that it does not interfere with its ecological function. That function is needed for the sustainability of development, even for human survival. Identifying strategic issues can help organizations, including in the public sector, pay attention to what is really important in long-term decision making. The purpose of this paper is to study the strategic issues of sustainable development in Sampang Regency, East Java Province.